PERAN PEMERINTAH KOTA SURABAYA DALAM PENGATURAN TRANSPORTASI PUBLIK KOTA SURABAYA: STUDI PERKOTAAN PROGRAM “SUROBOYO BUS” - M. Bayu Winaryo; Ucu Martanto (Jurnal Politik indonesia (Indonesian Journal of Politics), 2020)
The research focuses on the role of government institutions related to regulating public transportation in the city of Surabaya. Transportation is one sector which influences the economic growth of a city, the potential to be utilized as a commodity used in obtaining sources of power by some parties. Because in the practice of management, how a ruling regime is able to regulate, control and determine the direction of policy that will influence various efforts taken by the government to encourage economic growth from the region so as to be able to "turn on industrial machinery in its territory" and create new economic growth centers. Suroboyo Bus is also a manifestation of ongoing democracy in the city of Surabaya. In this study, we will explain several problems, first discussing the institutions involved in the process of forming a political decision related to the management of Suroboyo Bus, secondly about the interests involved in the political decision, the three relations that will emerge during the process. In this study it is known that the mayor is the institution that most determines the direction of policy that will be taken in the transportation sector in the city of Surabaya.